Formal Methods: Foundations and Applications 19th Brazilian Symposium, SBMF 2016, Natal, Brazil, November 23-25, 2016, Proceedings - Ribeiro, Leila; Lecomte, Thierry (Programming and Software Engineering,, 2016)
This book constitutes the refereed proceedings of the 19th Brazilian Symposium on Formal Methods, SBMF 2016, which took place in Natal, Brazil, in November 2016. The 12 papers presented together with two invited talks were carefully reviewed and selected from 22 submissions. They are organized in the following topical sections: analysis and verification; modeling and logic; and model checking.